Socio-Cultural Practices and Livelihood in the Amish Community of the USA - Sharma, Ajita Devi (NUTA Journal, 2024)
This study embarks on the Amish community's socio-cultural life patterns, which are religious and cultural groups. Global scenarios exceed the limits of technological innovations and people are abysmal in using them in their day-to-day operations and beyond the imagination of their limits. Most of the world is racing behind it but the Amish are the exception. They are conscious of stopping the brain drain process through their productive work as their life-guiding principles. The main objective of this article is to understand the Amish community and identify livelihood ideologies, and transformation among them. It attempts to understand the sociocultural significance of the Amish community by unraveling facts of their day-to-day practices. This article applies the qualitative method. Field visits, observation, interviews, and textual review are major tools and techniques. The article claims that many life-guiding principles in the Amish community could encourage outsiders to stop and think a minute about being Amish and to take benefits. Life-guiding principles could be learned from them. To be happy with the bonding of relationships and forgiveness character offers humanity a secret but very important gift. Many more unimagined and miraculous findings are mirrored through Amish life.